Modelling Telecentre as Community Learning Centre For Youths Using Triz - Amit, Pariyar; Narayanan, Kulathuramaiyer (2018)
Though telecentre projects such as Pusat Internet (PI) centres are widely deployed in Malaysia to provide equitable socio-economic benefits to the rural community using ICT, their social impacts are not fully exploited unless the rural youths are adequately and actively engaged in their programs or activities. One of the problems PIs or telecentres in general face is their inability to engage rural youths in local development via the offered programs. This leads to missed opportunity for youth empowerment and the subsequent development outcomes. To address this non-engineering social problem, we model telecentre as community learning centre for youths by applying TRIZ’s systematic approach to problem solving, rather than the standard community-based participatory action research (PAR) approach. We explore TRIZ tools such as functional analysis, cause and effect chain analysis, and engineering and physical contradictions. By applying inventive principles, the potential solutions suggested are modification of program structure and launching of Youth Profiling app. In the qualitative survey with 30 PIs, 70% agreed that the app can increase youth participation in PI programs, and thereby induce positive youth development and mobilize youth for the socio-economic development of their local community.